The Millennium Development Goals (MDG) ”“: a critical evaluation - Mibielli, Paulo; Barcellos, Frederico Cavadas (Sustainability in Debate, 2014)
The Millennium Development Goals (MDG) were adopted during the 56th Session of the General Assembly of the United Nations in 2001 as an offshoot of the Millennium Summit is considered the most successful effort the combating poverty. There is no doubt that the MDG were a success from the political point of view, especially for the UN that reached a projection in this area that has never been achieved before. The Sustainable Development Goals would not be on the agenda if the MDG were considered a failed experiment. The paradox is that its proposal to achieve a set of human development goals by 2015 was failed, despite all efforts. This paper aims to make a critical assessment of the MDG as its formulation and implementation, highlighting methodological and empirical issues.